2021
DOI: 10.14740/cr1179
|View full text |Cite
|
Sign up to set email alerts
|

Heart, Eye, and Artificial Intelligence: A Review

Abstract: Heart disease continues to be the leading cause of death in the USA. Deep learning-based artificial intelligence (AI) methods have become increasingly common in studying the various factors involved in cardiovascular disease. The usage of retinal scanning techniques to diagnose retinal diseases, such as diabetic retinopathy, age-related macular degeneration, glaucoma and others, using fundus photographs and optical coherence tomography angiography (OCTA) has been extensively documented. Researchers are now loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…AF is naturally linked to the eye through the vascular system. Some cardiovascular diseases have been found to be related to specific features of the retinal structure and microvessels, suggesting that microvessels and macrovessels are mutually affected in an interwoven manner in heart diseases ( 18 ). Consequently, it can be speculated that AF and IS may be presented with different pathological microscopic changes in the fundus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AF is naturally linked to the eye through the vascular system. Some cardiovascular diseases have been found to be related to specific features of the retinal structure and microvessels, suggesting that microvessels and macrovessels are mutually affected in an interwoven manner in heart diseases ( 18 ). Consequently, it can be speculated that AF and IS may be presented with different pathological microscopic changes in the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that some ocular symptoms of neuropsychiatric diseases occur up to 5 years before classical symptoms, and retinal pathological manifestations may precede symptoms of the brain ( 29 ). For instance, fundus vascular changes were reported several years before the onset of IS in chronic central diseases, while microvasculature and macrovasculature are affected in an intertwined manner ( 18 ). Therefore, it is assumed that the patients with IS have had microscopic pathological manifestations at least 1 year before stroke onset; however, these pathological symptoms cannot be observed by the naked eye, especially in the fundus blood vessels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI analysis based on fundus and retinal photographs can also be used to predict 48 cardiovascular and cerebrovascular diseases. Rim et al proposed a novel cardiovascular risk stratification system based on DL, their model called RetiCAC used 216,152 retinal photographs from five datasets as input and outperformed all single clinical parameter models in predicting coronary artery calcium, which is a marker of cardiovascular disease risk, and is also comparable to CT scan‐measured CAC.…”
Section: In Precision Medicinementioning
confidence: 99%
“…And based on data such as corneal topography, anterior segment OCT, and 3D images of the Pentacam anterior segment, several research teams[44][45][46][47] have successively developed multiple automatic grading methods for keratoconus using CNNs, with an accuracy of 99.3%. AI analysis based on fundus and retinal photographs can also be used to predict48 cardiovascular and cerebrovascular diseases. Rim et al proposed a novel cardiovascular risk stratification system based on DL, their model called RetiCAC used 216,152 retinal photographs from five datasets as input and outperformed all single clinical parameter models in predicting coronary artery calcium, which is a marker of cardiovascular disease risk, and is also comparable to CT scan-measured CAC.…”
mentioning
confidence: 99%